The Australian Embassy in Tokyo and Australia-Japan Relations - Darian-Smith, Kate; Lowe, David (ANU Press, 2023)
Relations between Australia and Japan have undergone both testing and celebrated times since 1952, when Australia's ambassadorial representation in Tokyo commenced. Over the years, interactions have deepened beyond mutual trade objectives to encompass economic, defence and strategic interests within the Indo-Pacific region and beyond. This 'special relationship' has been characterised by the high volume of people moving between Australia and Japan for education, tourism, business, science and research. Cultural ties, from artists-in-residence to sister-city agreements, have flourished. Australia has supported Japan in times of need, including the aftermath of the 2011 Tohoku earthquake. This book shows how the Australian embassy in Tokyo, through its programs and people, has been central to these developments. The embassy's buildings, its gardens and grounds, and, above all, its occupants-from senior Australian diplomats to locally engaged staff-are the focus of this multidimensional study by former diplomats and expert observers of Australia's engagement with Japan. Drawing on oral histories, memoirs, and archives, this volume sheds new light on the complexity of Australia's diplomatic work in Japan, and the role of the embassy in driving high-level negotiations as well as fostering soft‑power influences. 'With a similar vision for the Indo-Pacific region and a like-minded approach to the challenges facing us, Australia and Japan have become more intimate and more strategic as partners. I am very pleased to see this slice of Australian diplomatic history so well accounted for in this book.' - Jan Adams AO PSM, Secretary, Australian Department of Foreign Affairs and Trade; Australia's Ambassador to Japan, November 2020-June 2022